علم البلاغة كمدخل في تعليم اللغة العربية في اندونيسيا - Edy Murdani Z; Tika Mardiyah (Lugawiyyat, 2021)
Linguistic studies in language teaching do not get a dominant place, because the relationship between the two is not direct. Even if we look further, we find that what is taught can be said directly proportional to the meaning of the language itself, which is nothing but the study of linguistics as described by linguists. In the development that occurred, various theories were used in studying the phenomenon of language, one of which was the implicature theory. This theory requires that language be seen from its effects, so that words are arranged and spoken with the aim of giving implications for listeners. More than that, balagah in Arabic studies is wider in scope, because it requires context in speaking, who is the other person, to the choice of words and sentence phrases. In this case, balagah is a good internal approach in compiling, to developing teaching materials in teaching Arabic. With a strict approach, it is hoped that the language taught is actually used and adapted to the situation of students and teachers as part of the community members who use the language and who carry out the learning and teaching process.